TINGKAT KESIAPSIAGAAN KEPALA KELUARGA DALAM MENGHADAPI BENCANA GEMPA BUMI DI KECAMATAN PLERET DAN PIYUNGAN KABUPATEN BANTULTINGKAT KESIAPSIAGAAN KEPALA KELUARGA DALAM MENGHADAPI BENCANA GEMPA BUMI DI KECAMATAN PLERET DAN PIYUNGAN KABUPATEN BANTUL - Niken; Andri Setyorini (Jurnal Kesehatan Al-Irsyad, 2020)
Indonesia is one of the countries in the world that is vulnerable to various natural disasters. Indonesia is located at the confluence of three main plates of the earth, the Eurasian Plate, the Indo-Australian Plate and the Pacific Plate. One of the disasters that occurred in Indonesia was an earthquake, Yogyakarta is an area prone to experiencing earthquakes more precisely in Bantul district. In 2006 the earthquake in Yogyakarta claimed more than 6500 lives and property losses. The main factor in the emergence of many victims due to disasters is due to lack of knowledge about the disaster and lack of preparedness in anticipating the disaster. The purpose of this study was to measure the preparedness of the head of the family for earthquake disasters in the Piyungan and Pleret sub-districts of Bantul Regency. This type of research is in the form of quantitative descriptive by describing data that has been collected without intending to make conclusions that do not apply to the public. The number of samples is 192 head of family. Sampling of research using acidental sampling for the selection of male head of family respondents. The instruments used were LIPI and UNESCO in 2006. The results of research on the level of disaster preparedness in the majority Piyungan sub-district in the ready category (65-79) were 94 respondents (97.9%), while the Pleret sub-district included in the ready category (65-79) 90 respondents (93.8%). Suggestions from this research are to improve disaster preparedness by conducting training and simulations from the government, BPBD or involving health education institutions.